INTERPERSONAL CLIMATE AND STUDENTS’ ENGAGEMENT IN NIGERIA UNIVERSITY: A CONFIRMATORY FACTOR ANALYSIS APPROACH - Abubakar Yusuf, Habibat (Journal of Arts & Social Sciences, 2022)
The significant relationships that lecturers develop and maintain with their students in institutions cannot be overlooked as studies recognize it to have a positive impact on their academic outcomes. This study assessed lecturers interpersonal climate and students’ academic engagement in Nigeria university.  The study adopted the correlational design of the survey type.  The population for the study comprised all 49,153 undergraduate students of university of Ilorin, Nigeria. The required number of respondents for the study was ascertained using the Krejcie and Morgan table and 381 participants were chosen using a convenient sampling procedure. A self developed  survey instrument titled “Interpersonal Climate  and Students’ Engagement Survey” (ICSES) was constructed based on the focus of the study to gather primary data by means of empirical survey-based research methods which allows for the test of research hypotheses formulated for the study. ICSES scale was subjected to face and content validity and reliability coefficient of .89 obtained adjudged the instrument reliable.  The factors necessitating these interpersonal climate in school were explored and results show that except for the interrelation of the construct of shared vision on academic engagement with a low factor loading of .30, all other factors explored (Empathy, Leadership Pattern and compassion) were through measures of the constructs with high factor loading >.50 and have significant interactions with student engagement. The formulated hypothesis reveals that a significant relationship exist between the constructs understudied with p-value <.05. The implication of this findings as well as recommendations were highlighted in this study.